Penerapan Model Problem Based Learning Terhadap Hasil Belajar Subtema Bersyukur Atas Keberagaman - Tiara Rizkya Anwar; Yuyun Elizabeth; Abdul Gani, Resyi Abdul Gani (PT. Banjarese Pacific Indonesia, 2024)
Changes resulting from the learning process can be seen in the cognitive, affective, and psychomotor domains. The aim of this research is to determine differences in learning outcomes for the subthemes of plant growth and development through the Problem-Based Learning and Discovery Learning models. This research was carried out at Ciasmara 01 State Elementary School, Bogor Regency, Class IV A, and IV B in November, the odd semester. The research instrument uses pretest and posttest instruments which produce an N-Gain calculation for the Project Based Learning model of 80 with high criteria and an N-Gain value for the Problem Based Learning model of 73 with very high criteria. So the N-Gain in the experimental class with the Problem Based Learning model is greater than the control class with the Discovery Learning model. The researcher also carried out a normality test with the Lilliefors test for both samples having a normal distribution because the values for both samples were smaller than the L table. In the Problem-Based Learning class group, the value Lcount ≤ Ltable was obtained, namely 0.028 ≤ 0.189, and in the discovery learning class group, the value Lcount ≤ Ltable was obtained, namely 0.041 ≤ 0.189. Then, in the homogeneity test, the data is homogeneous because it is smaller than X2table, a value of 0.75 ≤ 5.991 is obtained. Furthermore, in the hypothesis test, the count of 7.29 was greater than the table of 2.01808, indicating that H0 (null hypothesis) was rejected and Ha (alternative hypothesis) was accepted. Based on the research results above, it can be stated that the problem-based learning and discovery learning models have differences in learning outcomes for the sub-theme of gratitude for diversity, in other words, the problem-based learning model is more effective than the discovery learning model for the sub-theme of gratitude for diversity.